Miguilim, Thiago e a estrada - Santini, Juliana [UNESP] (My University, 2012)
This work uses Bakhtin‟s concept of chronotope to analyze the literary narrative “Campo Geral”, by João Guimarães Rosa, and the filmic narrative Mutum, directed by Sandra Kogut. Therein, the figure of the road is considered as the starting-point for the observation of the way the relationship between time and space is constructed in both narratives.

Este trabalho utiliza o conceito de cronotopo, discutido por Mikhail Bakhtin, na análise da narrativa literária “Campo Geral”, de João Guimarães Rosa, e da narrativa fílmica Mutum, dirigida por Sandra Kogut. Sob esse aspecto, a figura da estrada é tomada como ponto de partida para a observação do modo como se cria a relação entre tempo e espaço em ambas as narrativas
Keywords: Narrative; Space; Time; Chronotope; Road; literatura brasileira; cinema